Linkages between technology choice and exporting: Evidence from Argentina - Gabriela Schmidt; Natalia Trofimenko (Kiel Institute for the World Economy (IfW), 2010)
This paper aids our understanding of the link between innovation and exporting behavior by detailing how firms may purposefully decide on the source country for the imported innovation and the market that they ultimately serve. We argue that firms who invest in the state-of-the-art technologies pursue a more aggressive exporting strategy and test this hypothesis with firm-level data from Argentina. The empirical results, based on the data from 1402 Argentinean firms over the period 1998-2001, suggest the existence of positive and highly significant effect of spending on new technology on the export performance. The magnitude of the effect is large: a one percent increase in spending on technology increases exports by 30 percent. The effect is even larger if the technology is sourced from one of the world's leaders: a one percent increase in spending on technology imported from leaders increases exports by 176 percent, whereas a one percent increase in spending on technology imported from non-leaders increases exports by about 28 percent.
Keywords: O3; F1; L1; 330; Technology Choice; Exporting; Productivity; Imports of Technology